CLINICAL AND HEMATOLOGICAL STUDY ON OVINE ANAPLASMOSIS IN SULAIMANI PROVINCE- IRAQ - Bahzad. H. salih Mustafa (Basrah Journal of Veterinary Research)
A study was carried out on Ovine Anaplasmosis in the Sulaimani province of Iraq from September to December2007. Five hundred thin blood smears were prepared form Peripheral blood of sheep in 10 different localities and stained by Giemsa. The prevalence of Anaplasma Ovis was 24 (4.8%) and the rate was highest 8.8% was among animals above 3 years. The infected animal showed mild fever, hyperpnoea and tachycardia. Hematological values of the infected sheep was as follows: Packed cell volume 22 ± 4.75 % , erythrocyte count 6.42 ± 1.35 ×106/ μl , hemoglobin concentration 6.95 ± 1.28 g/dl , mean corpuscular volume 35.5 ± 5.85/ fl , mean corpuscular Hemoglobin concentration 11..04 ± 2.42/ pg, mean corpuscular hemoglobin concentration 31.62 ± 6.62 g/dl and WBCs 11.15 ± 2.18× 10³ /μl , serum protein value 5.875 ± 0.801 mg/dl, serum calcium 8.341± 1.029 mg/dl, conjugate serum bilirubin 0.85 ± 0.314 mg/dl and serum cholesterol 57.291 ± 6.153 mg/dl.